Indocyanine Green-Enhanced Colorectal Surgery—between Being Superfluous and Being a Game-Changer - Catalin Alius; Corneliu Tudor; Cristinel Dumitru Badiu; Ana Maria Dascalu; Catalin Gabriel Smarandache; Alexandru Dan Sabau; Ciprian Tanasescu; Simona Andreea Balasescu; Dragos Serban (Diagnostics, 2020)
Nowadays, surgical innovations incorporate new technological conquests and must be validated by evidence-based medicine. The use of augmented reality-assisted indocyanine green (ICG) fluorescence has generated a myriad of intraoperative applications such as demonstration of key anatomical landmarks, sentinel lymph nodes, and real-time assessment of local blood flow. This paper presents a systematic review of the clinical evidence regarding the applications of ICG near-infrared (NIR) fluorescence in colorectal surgery. After we removed duplicate publications and screened for eligibility, a total of 36 articles were evaluated: 23 on perfusion assessment, 10 on lymph node mapping, and 3 on intraoperative identification of ureters. Lack of homogenous studies, low statistical power, and confounding evidence were found to be common amongst publications supporting the use of ICG in colorectal surgery, raising concerns over this seductive technique′s cost efficiency and redundancy. The compiled data showed that ICG NIR fluorescence may be a game-changer in particular situations, as proven for low colorectal anastomosis or lateral pelvic lymph node dissection, but it remains controversial for routine use and sentinel lymph node assessment. Further randomized studies are needed to confirm these conclusions. Future research directions include tumor-targeted fluorescence imaging and digital software for quantitative evaluation of fluorescence.